Smart Water Quality Measurement System Berbasis IoT untuk Peningkatan Efektivitas Pemantauan Kualitas Sumber Air - Winky Kurniawan; Muhammad Anwar (MASALIQ, 2025)
The increasing water pollution caused by domestic and industrial activities demands an efficient, real-time, and accurate water quality monitoring system. This study aims to design and develop a Smart Water Quality Measurement System based on the Internet of Things (IoT), capable of automatically monitoring pH, temperature, conductivity, and turbidity parameters, while transmitting the data to a server and website in real-time. The research employed an engineering approach using the Waterfall model, encompassing requirement analysis, system design, hardware and software implementation, testing, and evaluation. The system integrates digital pH sensor SEN-0131, temperature sensor DS18B20, conductivity sensor SEN-0171, and turbidity sensor SEN-0175 with the ESP32 microcontroller. Measurement data are displayed via the DSP-0004 LCD and transmitted to a MySQL database, which is then visualized through a PHP-based web interface. Testing was conducted on each sensor and the system as a whole. The results indicate that all sensors operated within acceptable accuracy tolerances, and the system consistently transmitted data over a three-hour testing period without interruption. The web interface also functioned responsively across various devices. The study concludes that the system successfully fulfills the requirements for efficient and real-time water quality monitoring. The implications highlight the significant potential of IoT technology in environmental management, with further development recommended, including the integration of additional sensors and automated notification features to enhance system functionality.